Gambaran Karakteristik Mahasiswa Dengan Asma Bronkial di Universitas Muhammadiyah Sukabumi Tahun 2024 - Risha Justisia Suhendar; Irawan Danismaya; Kartika Tarwati (Jurnal Anestesi, 2024)
Asthma is a chronic inflammatory disease that occurs in the airways, which can cause intermittent and reversible airflow disturbances, which can cause bronchial hyperreactivity to various stimuli, which can be characterized by recurrent episodic symptoms in the form of wheezing or what is usually called wheezing, coughing, shortness of breath and a feeling of heaviness. being in the chest mainly occurs at night or early in the morning. The aim of the research is to determine the characteristics of asthma patients among students, including gender, smoking and age. This research method is descriptive observational research with a cross-sectional approach. The subjects in this study were students with asthma in October 2023. Data was collected on 30 students at Muhammadiyah University of Sukabumi. The results of the study showed that students with asthma at Muhammadiyah University of Sukabumi in 2024 were more likely to be female (53.3%) than women. with males (46.7%), the patient's age was more likely to be 19 years old (50%), The percentage of students who do not smoke is (80%). And there are students with asthma whose frequency of asthma recurrence is 53%.